Growth Rates Analysis of Porites Corals from Nusa Penida, Bali - Camellia Kusuma Tito; Agus Setiawan; Sri Yudawati Cahyarini; Muji Wasis Indriyawan (Journal of Mathematical and Fundamental Sciences, 2016)
The annual growth of Porites coral is represented by a pair of high- and low-density bands. Environmental changes in the ambient waters influence the pattern of these annual density bands. Five colonies of Porites corals from Nusa Penida, Bali were investigated to analyze their annual linear growth rates using coral densitometry. From the analysis it was found that the annual linear growth rates of the colonies varied between 0.8924 to 1.0012 cm/yr. The trends of the colonies growth rates also varied. Two colonies showed a decreasing trend, while the others showed an increasing trend. The annual linear growth rates of most of the colonies were notinfluenced by sea surface temperature (SST); only one out of five colonies had a significant correlation with SST (R = 0.66, p-value < 0.05).